Metagenomic Insights into Microbial Signatures in Thrombi from Acute Ischemic Stroke Patients Undergoing Endovascular Treatment - Kasthuri Thirupathi; Sherief Ghozy; Abdullah Reda; Wasantha K. Ranatunga; Mars A. Ruben; Zarrintan Armin; Oana M. Mereuta; Sekhon Prabhjot; Daying Dai; Waleed Brinjikji; David F. Kallmes; Ramanathan Kadirvel (Brain Sciences)
Background: Variability in recanalization success during endovascular treatment for acute ischemic stroke (AIS) has led to increased interests in thrombus composition and associated cellular materials. While evidence suggests that bacteria may influence thrombus characteristics, limited data exist on microbiological profiles of thrombi in stroke patients. Objectives: Characterization of bacterial communities present in thrombi of AIS patients undergoing mechanical thrombectomy, providing insights into microbial contributions to stroke pathogenesis and treatment outcomes. Methods: Thrombi were collected from 20 AIS patients. After extracting metagenome, 16S rDNA sequencing was performed. Bioinformatic analysis included taxonomy and diversity assessments. The presence of bacterial DNA and viable bacteria in thrombi was validated using polymerase chain reaction (PCR) and bacterial culturing followed by matrix-assisted laser desorption ionization–time of flight (MALDI-TOF) analysis, respectively. Results: 16S rDNA was amplified in 19/20 thrombi (95%). Analysis identified a diverse microbial community, with Corynebacterium spp. as the most prevalent genus, followed by Staphylococcus spp., Bifidobacterium spp., Methylobacterium spp., and Anaerococcus spp. Alpha diversity analyses (Shannon index: 4.0–6.0 and Simpson index: 0.8–1.0) revealed moderate to high microbial diversity across samples; beta diversity demonstrated distinct clustering, indicating inter-patient variability in microbial profiles. PCR confirmed the presence of DNA specific to dominant bacterial taxa identified through sequencing. Culturing showed the presence of Staphylococcus epidermidis and Enterococcus faecalis in some clots as identified through MALDI analysis. Conclusions: This study shows bacterial communities present in AIS patients’ thrombi, suggesting a potential link between microbial signatures and thrombus characteristics.